PENGARUH METODE PEMBELAJARAN TERHADAP MINAT DAN PRESTASI BELAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Azizah, Azizah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
The low quality of student learning outcomes is caused by two factors, namely internal and external factors. Internal factors are experienced and internalized factors that affect students learning process and results include : attitudes toward learning, interest and motivation to learn, learning concentration, while external factors include suchthings as: the teacher as learning coaches, infrastructure and learning facilities, policies assessment, the social environment of students at school and at home as well as school curriculum. Learn something that attracts attention, would be more readily accepted than in studying things that do not attract attention, learning this also can not be underestimated or not important. In the case of interest, of course, someone who took an interest in a certain field will be easier to learn the field. Learning course will culminate with school performance achieved which will illustrate the success and success in learning . To achieve good learning, a lot of things that influence it, among others, the learning method used by teachers. Learning achievements will be achieved best when all factors support, such as teaching methods, with an interesting method which can be a bridge to reach the competencies.